Evidence for upregulation of excitatory synaptic transmission in the substantia nigra in Schizophrenia: a postmortem ultrastructural study - Brown, Nicole K.; Roche, Joy K.; Farmer, Charlene B.; Roberts, Rosalinda C. (Journal of Neural Transmission, 2023)
The dopamine hypothesis of schizophrenia suggests that psychotic symptoms originate from dysregulation of dopaminergic activity, which may be controlled by upstream innervation. We hypothesized that we would find anatomical evidence for the hyperexcitability seen in the SN. We examined and quantified synaptic morphology, which correlates with function, in the postmortem substantia nigra (SN) from 15 schizophrenia and 12 normal subjects. Synapses were counted using stereological techniques and classified based on the morphology of the post-synaptic density (PSD) and the presence or absence of a presynaptic density. The density and proportion of excitatory synapses was higher in the schizophrenia group than in controls, while the proportion (but not density) of inhibitory synapses was lower. We also detected in the schizophrenia group an increase in density of synapses with a PSD of intermediate thickness, which may represent excitatory synapses. The density of synapses with presynaptic densities was similar in both groups. The density of synapses with mixed morphologies was higher in the schizophrenia group than in controls. The human SN contains atypical synaptic morphology. We found an excess amount and proportion of excitatory synapses in the SN in schizophrenia that could result in hyperactivity and drive the psychotic symptoms of schizophrenia. The sources of afferent excitatory inputs to the SN arise from the subthalamic nucleus, the pedunculopontine nucleus, and the ventral tegmental area (VTA), areas that could be the source of excess excitation. Synapses with mixed morphologies may represent inputs from the VTA, which release multiple transmitters.